MO121: The Relationship between Perceived Stress with Anxiety, Depression, Sleep Quality, Insomnia and Drug Adherence in Patients with Systemic Lupus Erythematosus during the COVID-19 Pandemic. (3rd May 2022) - Gokmen, Kardelen; Barutcu Atas, Dilek; Tugcu, Murat; Velioglu, Arzu; Hakki Arikan, Izzet; Alibaz-Oner, Fatma; Direskeneli, Haner; Serhan, Tuglular Z; Asicioglu, Ebru
Abstract: BACKGROUND AND AIMS: Sleep disorders, depression and anxiety are commonly reported in patients with systemic lupus erythematosus (SLE). Public health emergencies such as pandemics can also increase these psychosocial distresses. Early diagnosis and treatment of these disorders will substantially affect patients' quality of life and medication adherence. The aim of this study was to evaluate both medication non-adherence and the incidence of perceived stress, anxiety, depression, sleep quality and insomnia during the COVID pandemic in patients with SLE. METHOD: This was a cross-sectional, descriptive survey study. A total of 211 participants, including 160 SLE patients aged 18 years and older and 51 healthy volunteers who were similar in age and gender, were included. A questionnaire of socio-demographics and COVID-19 status, Medication Compliance Reporting Scale (MARS-5), Perceived Stress Scale (PSS), Hospital Anxiety and Depression Scale (HAD-A and HAD-D), Pittsburgh Sleep Quality Index (PSQI) and Insomnia Severity Index (ISI) scales was assessed. The participants were interviewed face to face, and the answers were recorded by the researcher. RESULTS: The mean age of the patients was 41.85 ± 12.97 years and 142 (88.7%) of the patients were female. There was no significant difference between the patient and control groups in terms of the history of COVID-19 infection, symptoms and hospitalization. Fifty-nine (36.9%) patients had high perceived stress, 16 (10.0%) had anxiety, 45 (28.1%) had depression, 77 (48.1%) had poor sleep quality and 62 (38.8%) patients had insomnia. PSS (23.64 ± 7.86 versus 19.73 ± 4.80,   P  = .001), HAD-D (5.60 ± 3.40 versus 4.08 ± 2.21,   P  = .003), PSQI (6.31 ± 3.62 versus 4.43 ± 2.20,   P  = .001) and ISI (6.81 ± 4.98 versus 4.53 ± 2.83,   P  = .002) scores were significantly higher in the patient group than controls. Patients with PSS score ≥ 25 were categorized as patients with a high PSS score. Presence of anxiety, depression, poor sleep quality and insomnia were significantly higher in patients with a high PSS score. Medication non-adherence was detected in 79 (49.4%) of the patients. Interestingly, there was no difference in MARS-5 scores between high and low PSS groups. Comparison of baseline characteristics and clinical data of the patients according to PSS score is shown in Table 1 . The high PSS score was positively correlated with HAD-A, HAD-D, PSQI and ISI scores. Regression analysis revealed that high perceived stress is an independent predictor of depression [Exp(β) 95% CI: 1.488 (1.245–1.779), P  < .001], and anxiety [Exp(β) 95% CI: 1.235 (1.026–1.487), P  = .026]. CONCLUSION: SLE patients demonstrated increased levels of perceived stress, depression, poor sleep quality and insomnia compared to the healthy population during the COVID-19 pandemic. SLE patients with high perceived stress had more depression, anxiety, poor sleep quality and insomnia than those without. It needs to be determined whether these findings will have an impact on patient outcomes during long-term follow-up.